Sensitivity analysis of Pit characteristics in Urban Stormwater drainage design - Devkota, Bikash; Farzana, Dilruba; Ahammed, Faisal; Sharma Paudel Kafle, Sagun; Bhandari, Sandeepa; Wang, Zibing (Journal of Innovations in Engineering Education, 2025)
Stormwater management is one of the main increasing challenges of rapid urbanization, environmental deterioration, and climate change. Stormwater drainage systems have been using in urban areas for years to address those challenges. Suitable design and evaluation of that systems are needed to effectively manage floods in a specific area. Stormwater drainage systems of varied pit characteristics were analyzed in a residential area of the city of Onkaparinga in South Australia (SA) using DRAINS software to convey minor storm events of 20% annual exceedance probability (AEP) and major storm events of 1% AEP. Pit size and type, blockage factor, and pressure head loss coefficient were the properties of the pit considered in the sensitivity analysis. The outputs were compared in terms of maximum flow rate in pipes and hydraulic grade lines in pits. The results showed that the pit size and type were influential for stormwater management, whereas the blockage factor and pressure head loss coefficient could not be found to be sensitive to the design of water drainage systems considered in this study. Other drainage components and climate change impacts have been recommended in the future study. This research has set up a method that can be used by other city councils of SA to evaluate their practice of designing stormwater drainage systems. The findings from this research project can be beneficial for designers, researchers, managers, and planners of stormwater management.